Infrastructure in the Region: Long-Term Investments of Institutional Investors in Russia - BAKHAREVA, Olga Vladimirovna; ROMANOVA, Anna Ilyinichna; SAFINA, Roza Saimovna; KURSINA, Irina Mikhaiilovna; SHINDINA, Tatiana Aleksandrovna (Journal of Advanced Research in Law and Economics, 2017)
The article deals with the possibility of long-term investment in infrastructure development in the region at the expense of internal resources of the pension market of institutional investors (Pension Fund of Russia, private pension funds Vnesheconombank and private management companies). We have analyzed various theoretical and empirical studies that have shown the dependence of the financial sector and its impact on economic growth; analysis of the institutional changes in the pension system in Russia; analysis of the impact of the financial crisis of 2014 – 2015 on the results of the investment of institutional investors in the pension market. We offer for the development of the region to use economic mechanism of redistribution of pension assets and their direction in the development of the regional economy. The methodology of long-term investment of pension assets of State funded part of the pension system in infrastructure projects of regional economy through closed real estate funds will solve the problem of obtaining a stable private pension funds, investment income above the level of inflation and maintain purchasing power of the pension capital of the financial market. In addition to the accepted measures of federal social politics we suggest to use regional state support of institutional investors (investing  of infrastructural projects of region due to creation of bank of regional earth and their contributing to the closed funds of the real estate). The original typology of pension assets investment of institutional investors in infrastructure projects under the regional guarantee regional authorities (through standardized contractual pledge of land from the land bank in the region) would solve two pressing problems: the regional authorities will be able to access internal resources to long-term investments in their areas of the spatial development of the region and in infrastructure projects, and institutional investors will be able to ensure the growth of pension assets at the level of inflation in a closed real estate fund. Structural policy of the government on the development of the region, the implementation of infrastructure projects will improve access to markets and services and public goods firms in urban agglomerations and rural settlements, will contribute to the performance of the regional economy and promote economic growth in the region.